INDONESIAN UNIVERSITY STUDENTS’ MINDSET ABOUT THE ROLES OF TALENT AND EFFORT IN EFL LEARNING - Novita Herawati; Rahmah Fithriani (JOURNAL OF LANGUAGE, 2023)
Mindset plays a significant role in language learners' success. The present investigation examined the mindsets of Indonesian students with respect to their English language learning proficiency, specifically exploring whether such proficiency is attributable solely to innate talent or whether it requires individual effort. The primary objective of this study is to ascertain whether the mindset of individuals towards learning English is characterized by a growth orientation, which is influenced by effort, or a fixed orientation, which is influenced by talent. Additionally, the study seeks to explore the potential impact of this mindset on the motivation of individuals to study English. A sample of 150 university students from various academic disciplines was surveyed to gather data. The present investigation utilized a mindset survey, which was administered through the completion of a questionnaire and subjected to quantitative analysis. Based on the data, it can be inferred that students hold the belief that exerting effort is of greater significance than possessing innate talent when acquiring proficiency in the English language. This encompasses the capacity to endure critique and surmount obstacles and challenges. The present study characterizes the students’ attitude towards English as exhibiting a positive trend of progressing and developing, which is expected to yield enduring advantages for their English learning. They understand the significance of acquiring English proficiency for future employment opportunities and the diverse range of potential applications in their daily routines.